2019
DOI: 10.1021/acs.accounts.9b00111
|View full text |Cite
|
Sign up to set email alerts
|

Postcombustion Carbon Capture Using Thin-Film Composite Membranes

Abstract: Conspectus Climate change due to anthropogenic carbon dioxide emissions (e.g., combustion of fossil fuels) represents one of the most profound environmental disasters of this century. Equipping power plants with carbon capture and storage (CCS) technology has the potential to reduce current worldwide CO2 emissions. However, existing CCS schemes (i.e., amine scrubbing) are highly energy-intensive. The urgent abatement of CO2 emissions relies on the development of new, efficient technologies to capture CO2 from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 51 publications
1
47
0
Order By: Relevance
“…With ZIF-7 mixed into Pebax-2533, the melting point identified at the PTMO peak increased to approximately 294 K up to ZIF-7 35 wt% and decreased sharply at 50 wt%. Furthermore, the melting enthalpy of pure Pebax-2533 was similar to the values reported by J. Kim et al [31], and it was shown to decrease gradually with mixing with ZIF-7; we calculated the degree of crystallization using Equation ( 7) for a single substance and Equation (8) for the whole substance. The heat of fusion (∆H m • ) of PTMO and PA-12 was found to be 220 J/g [31,49] and 209 J/g [49,50], respectively.…”
Section: Properties Of Composite Membranessupporting
confidence: 79%
See 3 more Smart Citations
“…With ZIF-7 mixed into Pebax-2533, the melting point identified at the PTMO peak increased to approximately 294 K up to ZIF-7 35 wt% and decreased sharply at 50 wt%. Furthermore, the melting enthalpy of pure Pebax-2533 was similar to the values reported by J. Kim et al [31], and it was shown to decrease gradually with mixing with ZIF-7; we calculated the degree of crystallization using Equation ( 7) for a single substance and Equation (8) for the whole substance. The heat of fusion (∆H m • ) of PTMO and PA-12 was found to be 220 J/g [31,49] and 209 J/g [49,50], respectively.…”
Section: Properties Of Composite Membranessupporting
confidence: 79%
“…Thus, numerous attempts have been made to improve the affinity between polymer and particles, and there have been reports of improvements in existing pure membrane permeability properties by using them in an MMM. Unlike these MMMs, in TFC membranes manufactured with thin selective layers, permeability resistance decreases and permeability increases as the membrane gets thinner [5,7,8]. In general, thinning the selective layer in the membrane results in a decrease in the mechanical strength; therefore, it is manufactured by applying it on top of porous substrates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternative strategies to reduce the PE's environmental impact are seen in their minimised consumption during the membrane fabrication process. Various methods to deposit ultra-thin PEs layers have been reviewed recently (Liu, Nothling, Webley, Fu, & Qiao, 2019;Nikolaeva & Luis, 2020;Singh & Savoy, 2020;Zhang et al, 2020). The material and process optimisation yielded selectivities exceeding 100 with moderate permeances of approximately 10 GPU, surpassing the Robeson upper bound for C0 2 /N 2 .…”
Section: Introductionmentioning
confidence: 99%